2017
DOI: 10.13102/sociobiology.v64i2.1385
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sublethal Concentrations of Chlorpyrifos on Olfactory Learning and Memory Performances in Two Bee Species, Apis mellifera and Apis cerana

Abstract: Chlorpyrifos is a widely used organophosphorus insecticide. The acute oral 24 h median lethal dose (LD50) value of chlorpyrifos in Apis mellifera and in Apis cerana was estimated to assess differential acute chlorpyrifos toxicity in the two bee species. The LD50 values of chlorpyrifos in A. mellifera and in A. cerana are 103.4 ng/bee and 81.8 ng/bee, respectively, which suggests A. cerana bees are slightly more sensitive than A. mellifera bees to the toxicity of chlorpyrifos. Doses half the acute LD50 of chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 43 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…The results indicated that GmolGSTD1 may not be involved in the detoxification of these insecticides, which were inconsistent with the detoxification or resistance functions to insecticides of CpomGSTd2 of C. pomonella (Huang, Fan, Liu, & Feng, ), SlGSTE1 of Spodoptera litura (Xu, Zou, Zhang, Feng, & Zheng, ) and BdGSTe9 of Bactrocera dorsalis (X. P. Lu et al, ). Previous studies have shown that the insecticides can inhibit the sensitivities of insect olfactory system (Lalouette et al, ; Z. Li et al, ). For example, imidacloprid can significantly reduce the binding capacity of the odorant‐binding protein, AcerASP2, to host plant volatiles (G. Li et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that GmolGSTD1 may not be involved in the detoxification of these insecticides, which were inconsistent with the detoxification or resistance functions to insecticides of CpomGSTd2 of C. pomonella (Huang, Fan, Liu, & Feng, ), SlGSTE1 of Spodoptera litura (Xu, Zou, Zhang, Feng, & Zheng, ) and BdGSTe9 of Bactrocera dorsalis (X. P. Lu et al, ). Previous studies have shown that the insecticides can inhibit the sensitivities of insect olfactory system (Lalouette et al, ; Z. Li et al, ). For example, imidacloprid can significantly reduce the binding capacity of the odorant‐binding protein, AcerASP2, to host plant volatiles (G. Li et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The learning acquisition and short‐term retention of bees were assessed by the proboscis extension response (PER) method . A lemon odor was used as the conditioned stimulus, and a 40% sucrose solution (w/w) reward was used as the unconditioned stimulus (see Li et al ). Each experimental forager was tested in six PER trials.…”
Section: Methodsmentioning
confidence: 99%
“…The first five trials consisted of reinforced learning, to test short‐term learning acquisition, with a 10‐min interval in between. Experimental foragers were exposed to the lemon odor for 3 s, and then immediately exposed to both the lemon odor and the sucrose solution for another 3 s. The timing and duration of the lemon odor and sucrose solution were accurately controlled by an air‐pump device . The sixth trial was performed 2 h after the fifth trial to test the short‐term retention ability.…”
Section: Methodsmentioning
confidence: 99%
“…Permethrin, found only in wax samples, is also somewhat toxic to bees 29,33 but it was reported from at least one sample from all original landscapes in both years, so its occurrence would not explain landscape differences. A fourth example, chlorpyrifos, is comparatively toxic to bees 29,33 and has been found to affect learning behavior at sublethal concentrations 34 . Chlorpyrifos was detected in beebread in August (both years) only from colonies in the AG group, and again in samples taken in March only from colonies used for almond pollination.…”
Section: Sample Date Agrochemicalmentioning
confidence: 99%